Superconducting behavior of BaTi2Bi2O and its pressure dependence. Issue 40 (9th October 2020) - Wang, Yanan; Li, Huan; Taguchi, Tomoya; Suzuki, Ai; Miura, Akari; Goto, Hidenori; Eguchi, Ritsuko; Miyazaki, Takafumi; Liao, Yen-Fa; Ishii, Hirofumi; Kubozono, Yoshihiro
Abstract : A possible Dirac semimetal, BaTi2 Bi2 O, indicates a sign of topologically nontrivial nature in superconductivity at high pressure. Abstract : A new superconducting sample, BaTi2 Bi2 O, was synthesized and characterized over a wide pressure range. The superconducting transition temperature, T c, of BaTi2 Bi2 O was 4.33 K at ambient pressure. The crystal structure was tetragonal (space group of P 4/ mmm (No. 123)), according to the X-ray diffraction (XRD) pattern at ambient pressure. The XRD pattern was analyzed using the Le Bail method. The magnetic-field dependence of the magnetization at different temperatures was precisely investigated to elucidate the characteristics of the superconductivity. The pressure-dependent XRD patterns showed absence of structural phase transitions up to 19.8 GPa. The superconducting properties of BaTi2 Bi2 O were investigated under pressure. T c monotonously increased with the pressure ( p ) up to 4.0 GPa and saturated above 4.0 GPa. The variations in the T c – p plot were thoroughly analyzed. The Cooper pair symmetry (or superconducting pairing mechanism) was analyzed based on the magnetic field dependence of the superconductivity at ambient and high pressures, which indicated a sign of p -wave pairing for the superconductivity of BaTi2 Bi2 O, i.e., topologically nontrivial sign was suggested for BaTi2 Bi2 O.